TEMPO-mediated oxidation of polysaccharides: An ongoing story. (1st June 2017) - Pierre, Guillaume; Punta, Carlo; Delattre, Cédric; Melone, Lucio; Dubessay, Pascal; Fiorati, Andrea; Pastori, Nadia; Galante, Yves M.; Michaud, Philippe
Highlights: Recent insights into TEMPO chemistry applied on polysaccharides are reviewed. This chemistry gives birth to polyuronides with various biological applications. Oxidized cellulose derivatives have mechanical and physico-chemical properties. The biodegradability potential of oxidized polysaccharides is of first interest. Abstract: The oxidation of natural polysaccharides by TEMPO has become by now an "old chemical reaction" which led to numerous studies mainly conducted on cellulose. This regioselective oxidation of primary alcohol groups of neutral polysaccharides has generated a new class of polyuronides not identified before in nature, even if the discovery of enzymes promoting an analogous oxidation has been more recently reported. Around the same time, the scientific community discovered the surprising biological and techno-functional properties of these anionic macromolecules with a high potential of application in numerous industrial fields. The objective of this review is to establish the state of the art of TEMPO chemistry applied to polysaccharide oxidation, its history, the resulting products, their applications and the associated modifying enzymes.